Refraction effect in the heat flow due to a 3-D prismoid, situated in a two-layered earth - HVOŽDARA, Milan (Contributions to Geophysics and Geodesy, 2021)
We present a mathematical model for the disturbance of the stationary geothermal field due to a three-dimensional perturbing body embedded near the surface of a two-layered earth. The theoretical analysis is based on the generalized theory of the double-layer potential, similar to the boundary integral method used in the direct current geoelectricity problems. Special attention is paid to the quadrilateral prismoids bounded by planar skew faces. The numerical calculations were performed for a 3-D prismoids (blocks) with thermal conductivity greater or lower than in the ambient layer. Numerous graphs are shown for the disturbance of the heat flow on the surface of the Earth.